2014
DOI: 10.2147/ijn.s68582
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of bioactive conjugated near-infrared fluorescent proteinoid-poly(L-lactic acid) hollow nanoparticles for optical detection of colon cancer

Abstract: Colon cancer is one of the major causes of death in the Western world. Early detection significantly improves long-term survival for patients with colon cancer. Near-infrared (NIR) fluorescent nanoparticles are promising candidates for use as contrast agents for tumor detection. Using NIR offers several advantages for bioimaging compared with fluorescence in the visible spectrum: lower autofluorescence of biological tissues and lower absorbance and, consequently, deeper penetration into biomatrices. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Until recently, most of the reported proteinoids in the literature were synthesized from at least seven amino acids and possessed relatively low molecular weights with higher PDIs (above 1.5), as common for step-growth polymerization mechanism [28]. The high molecular weights shown in the present study indicate that the polymerization procedure used here may provide relatively long polymer chains which resemble long proteins [29]. Long polymers usually possess improved mechanical properties than short ones, due to the increased number of physical interactions between the polymer chains [23].…”
Section: Freeze-drying Of Proteinoid Particles For Long-term Storagementioning
confidence: 66%
See 2 more Smart Citations
“…Until recently, most of the reported proteinoids in the literature were synthesized from at least seven amino acids and possessed relatively low molecular weights with higher PDIs (above 1.5), as common for step-growth polymerization mechanism [28]. The high molecular weights shown in the present study indicate that the polymerization procedure used here may provide relatively long polymer chains which resemble long proteins [29]. Long polymers usually possess improved mechanical properties than short ones, due to the increased number of physical interactions between the polymer chains [23].…”
Section: Freeze-drying Of Proteinoid Particles For Long-term Storagementioning
confidence: 66%
“…This self-assembly process may be utilized to encapsulate different suitable molecules within the core of the particles, achieving a biocompatible drug carrier [27]. In recent studies, our group used this procedure to encapsulate anti-cancer drugs and near infrared fluorescent dyes within nano-sized particles for cancer therapy and detection [24,28,29].…”
Section: Size and Size Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, one of the near-infra-red fluorescent proteinoidpoly(L-lactic acid)(PLLA) NPs preparation was described where a P(EF-PLLA) random copolymer was prepared using thermal copolymerization of L-phenylalanine(F), L-glutamicacid(E), and PLLA (Kolitz-Domb et al, 2014). The study revealed that under optimal conditions, the proteinoid-PLLA copolymer can self-assemble into hollow nano-sized particles that can be used to encapsulate the indocyanine green and NIR dye.…”
Section: Other Nanoparticles In Colorectal Cancer Detection and Treatmentmentioning
confidence: 99%
“…NIR fluorescent NPs are also considered promising candidates for use as contrast agents for tumor detection (Ren et al, 2015). Kolitz-Domb et al (2014) demonstrated that bioactive conjugated NIR fluorescent proteinoid-poly (L-lactic acid) hollow NPs can be used for optical detection of colon cancer in a chicken embryo model. Will et al.…”
Section: Unique Physical and Chemical Properties Of Nanomaterialsmentioning
confidence: 99%